Physically Compromised and Physically Talented Children in Northeastern Slovenia - Planinšec Jurij; Matejek Črtomir (University of Maribor Press, 2012)
The aim of our research was to determine the share of physically compromised and physically talented children in northeastern Slovenia. The sample comprised 621 children aged nine to eleven years, among which there were 316 girls (M=10; SD=0.8) and 305 boys (M=10; SD=0.81). In order to assess their motor skills, seven different tests were used, mostly from Eurofit test battery, which covered explosive power, repetitive power balance, eye-hand coordination, speed of simple movements, whole body coordination, and endurance. The assessment was made for each physical fitness test separately. The cut-off points for determination of physically compromised and physically talented children were set at -1SD and +1SD, respectively. The results of all physical fitness tests showed that the share of physically compromised children exceeded ten percent for both genders. The largest number of boys and girls were physically compromised with regard to endurance and balance, respectively. On the other hand, boys proved to be most physically talented with regard to endurance, and girls with regard to explosive power. Gender differences were most obvious with regard to general endurance, as 21 per cent of the boys were physically compromised as opposed to 13 per cent of the girls. As for physical talent, we observed less gender-related differences. The results indicate increasing differences in physical fitness among children from northeastern Slovenia. The implementation of curricular and extracurricular sports activities should aim at reducing the number of physically compromised children. On the other hand, it would make sense to encourage physically talented children to get involved in organized forms of exercise.